Comparison of Two Donor Liver Procurement Methods for Treatment of Pediatric Acute Liver Failure - Pei, Jiahao; Shen, Conghuan; Li, Ruidong; Tao, Yifeng; Lu, Lu; Chen, Weiming; Xie, Xinbao; Wang, Zhengxin (Frontiers in Pediatrics, 2022)
Background: To evaluate difference and efficacy of two donor liver procurement methods for treatment of pediatric acute liver failure (PALF) by living donor liver transplantation (LDLT). Methods: 17 patients (12 males, five females) with PALF who underwent LDLT in our hospital between October 2016 and October 2020, and prognostic efficacy of donors and recipients using two donor liver procurement methods was analyzed. Results: The donors and recipients were both divided into laparoscopic (7 cases) and open (10 cases) donor liver procurement groups. In the recipients, two deaths occurred in laparoscopic group and one in open group, three postoperative complications in laparoscopic group and six in open group. The cumulative 1-year and 3-year survival rates in laparoscopic group and the open group were 80.0% and 85.7% separately. There was no difference in the postoperative survival and complications rates between the two groups. In the donors, the operation time, postoperative hospital stay and blood loss of laparoscopic group was significantly reduced compared with open group (P<=0.01).No death or serious complication occurred in either donor group. Conclusion: Laparoscopic donor liver procurement is worth recommending than open donor liver procurement for treatment of PALF combined with LDLT in qualified transplant centers.